Systematic literature review of food-related translation from 2004 to 2024 - Zhang, Qi; Ang, Lay Hoon; Yasin, Megat Al Imran (Academy Publication, 2025)
Despite the wide recognition of food as an essential human necessity and cultural representation of a country in multiple disciplines, its exploration within translation studies remains under-researched. Therefore, a comprehensive review of food-related translation is vital. The current research systematically reviews previous studies on food-related translation in the past two decades (2004-2024) by searching relevant literature in two databases: Web of Science and Scopus. Through pre-defined screening criteria, along with analysis of titles, abstracts, keywords, and full papers (when necessary), 85 pertinent publications were identified and examined in terms of annual distribution, research types, research methods, textual types, and research contents. The main findings suggest that the academic interest in food translation initially peaked around 2015-2016, followed by a period of irregular fluctuations in publication volume, with a notable surge observed in the most recent three years (2022-2024). Furthermore, the results indicate a predominance of empirical research over non-empirical one, with qualitative research being dominant followed by mixed research. Additionally, the findings reveal that research into food-related translation spans a variety of textual types, ranging from early printed restaurant menus and literary texts to more contemporary genres such as audiovisual products, mobile applications, and video games, with a special focus on the exploration of translation strategies employed when rendering dish names from one language to another. This study contributes to the existing literature by identifying the research gaps and trends, as well as providing corresponding recommendations for future researchers to study food-related translation.